Bimbingan Manasik untuk Meningkatkan Kesiapan dan Penguatan Spiritual Calon Haji dalam Meraih Kesempurnaan Ibadah - Laily, Uut Nur; Aisyah, Siti; Lativa, Lativa; Masluchah, Ifa (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The aim of this service is to increase the readiness and spiritual strengthening of prospective Hajj pilgrims in Nganjuk Regency in 2024 through manasik guidance. Service methods include preparing comprehensive presentation materials, group discussion sessions, and the use of visual media to facilitate understanding of the procedures for the Hajj pilgrimage and strengthening spiritual intentions. This activity was carried out in Kertosono, Patianrowo, Lengkong, and Jatikalen sub-districts on April 30, 2024, with the active participation of 70 participants. The results showed a significant increase in participants' understanding of the Hajj procedures, strengthening spiritual awareness and mental readiness to face the Hajj journey. Apart from that, this activity also succeeded in building a social environment that supports spiritual growth among participants, creating momentum for a deeper and more sustainable spiritual transformation in preparation for their Hajj pilgrimage.